IMPLICATIONS OF INSIDER AND OUTSIDER CEOs ON FIRM PERFORMANCE: EVIDENCE FROM CEO SUCCESSIONS FROM TURKEY - Aylin Ataay (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study investigatesthe performance consequences of Chief Executive Officer (CEO) succession in anemerging market as prior research suggests that the differences in theperformance implications of CEO successor’s origin may be related to the distinctivecontexts offered by these economies. Hence, we investigated the impact of a newCEO origin on firm profitability in Turkey for the years 2010 and 2011. Theresults showed that there is a positive association between outsider successorsand post-succession profitability in listed companies in Turkey. Further, theeffects of unrelated and related outside succession on post-succession firmperformance differ. While the related outsiders affect negatively the firmperformance, unrelated outsiders contribute positively to the post-successionprofitability (ROA). These findings thus contribute to the existing CEOsuccession literature by emphasizing the value of outsider CEOs’ freshperspectives, new and diverse skills and initiative for change.